2022
DOI: 10.1302/0301-620x.104b3.bjj-2021-1320.r1
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fluid calprotectin performs better than synovial fluid polymerase chain reaction and interleukin-6 in the diagnosis of periprosthetic joint infection

Abstract: Aims The preoperative diagnosis of periprosthetic joint infection (PJI) remains a challenge due to a lack of biomarkers that are both sensitive and specific. We investigated the performance characteristics of polymerase chain reaction (PCR), interleukin-6 (IL6), and calprotectin of synovial fluid in the diagnosis of PJI. Methods We performed systematic search of PubMed, Embase, The Cochrane Library, Web of Science, and Science Direct from the date of inception of each database through to 31 May 2021. Studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…This investigation had several limitations: 1) it was a single-centre retrospective study with a limited sample size and selection bias, and the conclusions need to be further verified by multicentre and large samples; 2) we observed that patients in the RA group were more often female (although this constitutes a potentially sex-confounding bias, the prevalence of RA in women is known to be higher in general, not only in our study population); 3) not all patients performed the synovial fluid tests, resulting in a small sample size of synovial fluid in our study; 4) patients who took antibiotics selfprophylactically before admission were not excluded, which may have lowered the predictive power of the detection indexes; 5) since it was a retrospective study, the bloody synovial fluid samples in this study were not calculated using the adjusted synovial WBC formula; and 6) the observation index is limited, so it is necessary to further explore the value of other markers, such as interleukin 6 (IL-6), synovial fluid alpha-defensin, and synovial fluid calprotectin, [44][45][46] for diagnosing RA-PJI in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This investigation had several limitations: 1) it was a single-centre retrospective study with a limited sample size and selection bias, and the conclusions need to be further verified by multicentre and large samples; 2) we observed that patients in the RA group were more often female (although this constitutes a potentially sex-confounding bias, the prevalence of RA in women is known to be higher in general, not only in our study population); 3) not all patients performed the synovial fluid tests, resulting in a small sample size of synovial fluid in our study; 4) patients who took antibiotics selfprophylactically before admission were not excluded, which may have lowered the predictive power of the detection indexes; 5) since it was a retrospective study, the bloody synovial fluid samples in this study were not calculated using the adjusted synovial WBC formula; and 6) the observation index is limited, so it is necessary to further explore the value of other markers, such as interleukin 6 (IL-6), synovial fluid alpha-defensin, and synovial fluid calprotectin, [44][45][46] for diagnosing RA-PJI in the future.…”
Section: Discussionmentioning
confidence: 99%
“…While further research on calprotectin is necessary, according to recent diagnostic meta-analyses [ 117 , 118 ] synovial calprotectin has the potential to be a promising biomarker for diagnosing PJI due to its benefits, including its high diagnostic accuracy and convenience. However, it is important to note that current data are insufficient in order to be able to consider synovial calprotectin as a suitable stand-alone diagnostic marker for PJI.…”
Section: Diagnostic Testsmentioning
confidence: 99%
“…Additionally, the synovial IL-6 level does not provide any additional benefit in the diagnosis of PJI [ 59 ]. Again, in a meta-analysis published in 2022 supporting these findings, it was stated that the synovial fluid IL-6 level may be more useful as a confirmatory biomarker rather than as a diagnostic biomarker [ 60 ].…”
Section: Biomarkers In Synovial Fluidmentioning
confidence: 99%